The Teaching of Sports Physical Education Skills under Exercise Physiology Based on Support Vector Machine - Zhen Jiang (Discrete Dynamics in Nature and Society)
As the core component of a physical education teacher’s professional skills, sports skills are the precondition for physical education teachers to teach and also a key factor for the level of a physical education teacher’s professional skills. According to the survey, the current sports skills of graduates majoring in physical education are not satisfactory, and a considerable number of students think that their sports skills are difficult to meet the needs of educational practice. In the era of basic education reform and teacher professional development, we analyze the advantages and make up for the deficiencies in order to improve the effect of physical education professional sports skills training and meet the society’s needs for high-skilled sports talents. The experiment randomly selected five physical education students from five schools and five students as the research objects. Based on the support vector machine, the questionnaire survey method, interview method, and statistical method are used to conduct related research and analysis on it. The results show that sports skills are the advanced stage of sports technology development. At present, there are many sports skills that students learn in major colleges and universities, but they really master the sports skills. Motor skills are rare. At present, the future talents of physical education major are mostly “compound” and “specialized” talents, and there are few references to applied talents. The training objectives should be clear, the curriculum should be closely linked to the training objectives, the selection of skills teaching methods by teachers should be adapted to the teaching content, and teachers and students should be actively active among these elements, which are both used and influenced by these elements.